Anxiety perception in BMX cross athletes based on gender and competition levels: A descriptive analysis using SAS-2 - Anne, Rere; Komarudin; Saputra, Mochamad Yamin; Novian, Geraldi (Journal Sport Area, 2026)
Background: Many BMX cross athletes experience high levels of anxiety before competing. While there is a wealth of research on anxiety in other sports, research specifically examining anxiety perceptions in BMX cross-athletes, taking gender and competition level into account, is limited. Objectives: This study aims to analyse the perception of anxiety of BMX cross-athletes in competition, viewed from gender and competition class. Methods: The method used is quantitative descriptive using the Sport Anxiety Scale-2 (SAS-2), which consists of 15 items and is divided into three main subscales, namely somatic, worry, and concentration disorders. Data analysis was conducted using SPSS Version 29 to determine the percentage of anxiety perception and differences in each gender and competition level. Subjects involving 18 BMX cross athletes in Bandung City aged 16.94 ± 3.404 years. Data analysis was carried out by presenting the percentage of results. Results: The results showed that BMX Cross athletes had a moderate level of anxiety, with a mean score of 2.43 ± 0.58 based on the SAS-2 scale (1–4). Descriptively, female athletes showed slightly higher mean anxiety scores than male athletes. Based on competition class, athletes in higher categories (U-23 and elite) tended to have higher mean anxiety scores compared to junior and challenge levels. However, these findings are descriptive only and should be interpreted with caution. Conclusion: This study concluded that BMX cross athletes have moderate levels of anxiety. Coaches and sports psychologists are encouraged to implement mental management training to further support athletes in stressful situations. Future studies should include larger, more diverse samples and examine additional factors to deepen our understanding of anxiety in BMX cross athletes.